The branches of ecology a 20th century history - Egerton, Frank N. (CRC Press, an imprint of Taylor & Francis Group, LLC, 2023)
"Ecology grew from a minor science, in 1900, into a major discipline in the 20th century. This book describes this development. A dramatic increase in ecological knowledge was accompanied by the formation of ecological professional societies. Universities added ecologists to their faculties. And governments acknowledged the need for ecologists to advise on conservation of natural resources and to combat pollution. Ecology is still growing as a discipline and many local, regional and global environmental problems remain to be studied. Just how ecologists rose to these challenges is an exciting and inspiring narrative, which is the theme of this book"--Provided by publisher.